Impact of the National Economic Recovery (PEN) Policy in The Economic Growth of The Province of Maluku Post-Covid-19 - Rukmuin Wilda Payapo (Budapest International Research and Critics University, 2022)
This research aim is to evaluate the impact of the National Economic Recovery policy on the Economic Growth of Maluku Province after the Covid-19 pandemic. This research is qualitative research using a case and field study approach. Data collection techniques are observation and literature review. The results showed that after passing the peak of the economic crisis due to the Covid-19 pandemic in 2020 with economic growth contracting reaching 0.92 percent (yoy), Maluku Province has been able to achieve positive economic growth in 2021 of 3.04 percent (yo). A success that can be felt as a result of the implementation of the National Economic Recovery (PEN) measures. Government policy insocial safety nets, support for MSMEs, job creation through structural reforms by the Job Creation Act, and harmonization of tax regulations as a form of transformation from a fiscal perspective have had a positive impact on the economic growth of Maluku Province in the post-Covid-19 pandemic. The success of getting through the storm of the economic crisis shows that the National Economic Recovery (PEN) policy has had a huge impact on the recovery of the Regional Economy. The momentum for economic recovery in Maluku Province must be maintained with a high level of vigilance, because the development of the corona virus mutation can occur at any time, and it will be a threat to regional economic growth.